CONSIDERING LIBERTARIANISM FROM THE PERSPECTIVE OF ANALYTIC POLITICAL PHILOSOPHY - N. N. Ravochkin (Дискурс)
The article reviews libertarianism, which is a modern political concept that has a liberal ideological background. Analytic tradition has been chosen as a theoretical and methodological basis, representing the set of views that emerged in the last century as a reaction to classical types of philosophising, and indicated the prospect of studying political and legal subjects. The author focuses on the views of Bose, Nozick, Rawls and Hayek. Differences in views of libertarians from those of liberals and conservatives are presented. The analysis of the key concept of "freedom" led to the insight that its purpose is to achieve individual goals. It is established that libertarianism takes into account negative influence of state on socio-political existence due to totalitarian systems formation. In this regard it is necessary to take into account a new basis that denies the dominant role of state and law in public life, which indicates their possible further transformations.